An association between calcium channel blocker and breast cancer in patients with hypertension: A case-control study - Ratchata Supannaroj; Sittichai Khamsai; Jarin Chindaprasirt; Wattana Sukeepaisarnjaroen; Panita Limpawattana; Kittisak Sawanyawisuth (Elsevier, 2023)
Hypertension is a common disease in clinical practice. Calcium channel blocker (CCB) is an effective antihypertensive agent. There is inconsistent data of an association of CCB and breast cancer in literatures particularly in breast cancer cytology. This study aimed to evaluate this association by a case-control design. The inclusion criteria were adult patients with an age of 18 years or over, diagnosed as hypertension, with a result of mammogram. Those who were pregnant, had no pathological results, or had breast mass prior to diagnosis of hypertension were excluded. Cases defined if the pathological report of any types of breast cancer, while controls were those with benign breast mass. Factors associated with breast cancer were calculated by logistic regression analysis. There were 299 patients met the study criteria. Of those, 100 patients (33.4 %) were in the case group or breast cancer group. There were three factors independently associated with breast cancer. CCB treatment had adjusted odds ratio of 2.25 (95 % confidence interval of 1.36, 3.77), while age of 50 years old or over and hormonal therapy also independently associated with breast cancer with adjusted odds ratios of 3.41 and 2.91, respectively. The CCB group had significantly higher proportion of ductal breast cancer than those who did not take CCB (42.5 % vs 23.8 %, p < 0.001). CCB treatment may be associated with breast cancer especially ductal carcinoma in this study population.